2011
DOI: 10.1016/j.carbpol.2010.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inclusion complex of zerumbone with hydroxypropyl-β-cyclodextrin

Abstract: In this paper we investigated the inclusion complexation between zerumbone (ZER) and hydroxylpropyl-cyclodextrin (HPCD) at four different temperatures: 293-318 •K. The thermodynamic parameters (H, S and G) for the formation of the complex were obtained from the van't Hoff equation. The complex with HPCD was characterized by differential scanning calorimetry (DSC), X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FT-IR), and molecular modeling using PM6. The solubility of ZER was enhanced >3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…It has been demonstrated when a molecule forms an inclusion complex with a cyclodextrin, there is a shifting or a disappearance of the melting point peak 18,19 . Figure 4 presents the DSC diagrams of EB, 1:1 physical mixture and inclusion complexes.…”
Section: 3-differential Scanning Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated when a molecule forms an inclusion complex with a cyclodextrin, there is a shifting or a disappearance of the melting point peak 18,19 . Figure 4 presents the DSC diagrams of EB, 1:1 physical mixture and inclusion complexes.…”
Section: 3-differential Scanning Calorimetrymentioning
confidence: 99%
“…However, the XRD patterns of the co-evaporated and spray dried complexes showed a complete absence of crystalline peaks, suggesting the formation of a new structure, in which EB probably is included in the hydrophobic cavity of HP-β-CD. It is described that a lack of crystallinity is indicative of the formation of an inclusion complex [18][19][20] . 3.6.-Maximum solubility of the inclusion complexes at pH 8 EB is a basic drug whose solubility is reduced at higher pH, and this characteristic can be a drawback when the drug is administered to salmons through medicated foods.…”
Section: 4-ft-ir Spectroscopymentioning
confidence: 99%
“…This allows the construction of three-dimensional models of drug-CD complexes, visualization of structural integrity, and intra-and intermolecular interactions (Seridi, Boufelfel, 2011;Leila et al, 2011;Eid et al, 2011;Ge et al, 2011;Mishur et al, 2011).…”
Section: Formation Of Inclusion Complexesmentioning
confidence: 99%
“…FTIR spectra of the inclusion complex and those for pure compounds as well as the physical mixture are shown in corresponding to C=O stretching vibration shifted to 1752 cm -1 and the intensity decreased. The observed changes in the FTIR spectra of LIG complexed with HP-b-CD are due to a restriction of the vibration of the LIG molecule upon its encapsulation into the HP-b-CD cavity (23). Therefore, the FTIR spectroscopy result indicated that the inclusion complex of LIG with HP-b-CD was obtained.…”
Section: Ftir Spectroscopymentioning
confidence: 81%